Vitamin A Promotes Leydig Cell Differentiation via Alcohol Dehydrogenase 1 - Yang, Yan; Luo, Jiao; Yu, Dan; Zhang, Tiantian; Lin, Qilian; Li, Quan; Wu, Xupeng; Su, Zhijian; Zhang, Qihao; Xiang, Qi; Huang, Yadong (Frontiers in Endocrinology, 2018)
Vitamin A (retinol) is important for multiple functions in mammals. In testis, the role of vitamin A in the regulation of testicular functions is clearly involved in rodents. It is essential for sperm production. Vitamin A deficiency adversely affects testosterone secretion. Adult Leydig cells are responsible for testosterone production in male. The role of vitamin A in regulating the differentiation of Leydig cells is still unknown. In this study, we explored the roles and underlying mechanisms of vitamin A in Leydig cell differentiation. We found that vitamin A could regulate the Leydig cells differentiation. Leydig cell differentiation is adversely affected in mice maintained on a vitamin A-free diet. This effect is mediated by alcohol dehydrogenase 1 (ADH1). ADH1 could increase retinoic acid (RA) synthesis, then RA facilitates Leydig cell differentiation by activating the steroidogenic factor 1 gene (Nr5a1) promoter activity, which consequently promotes Leydig cell specific gene expression, resulting in progenitor Leydig cells differentiation into functional Leydig cells. This is the first study connecting a metabolic enzyme of retinol (ADH1) to the the regulation of Leydig cell differentiation, which will provide experimental evidence for the development of therapeutics to promote Leydig regeneration through the administration of a RA signaling regulator or a vitamin A supplement.